(untitled) (CIPEEX, 2025)
The introduction of solid foods begins after the breastfeeding period, which begins in the sixth month of a child’s life. This is a very important phase that determines formation and development. It focuses on the first two years, as this period will define patterns that will last a lifetime. Food preferences will be determined by the assimilation of both environmental factors (region, customs, conditions, traditions) and genetic factors (parents’ habits, diet during pregnancy, and individual factors). Marque et al., 2020. In theory, healthy eating should be introduced and encouraged in the early stages of a child’s life, respecting the six-month period when adaptation and complementary feeding begin. According to the Family Budget Survey, Brazilian children lack foods such as fruits, vegetables, and greens, demonstrating an excessive consumption of processed foods, such as processed foods, sugary drinks, cookies, snacks, and popcorn (Oliveira et al. 2017). Obesity is one of the biggest public health challenges in Brazil, associated with comorbidities such as diabetes, dyslipidemia, hypertension, and cardiovascular disease. Its main cause is the high consumption of ultra-processed foods and low physical activity. Furthermore, the excessive use of technology and social media has contributed to childhood obesity, as it affects eating habits and reduces the participation in outdoor activities. Ultra-processed foods, which are inexpensive, easily accessible, and well-accepted, represent a large portion of caloric intake, especially in Brazil. Adequate nutritional introduction is essential to prevent childhood obesity. The World Health Organization (WHO) recommends exclusive breastfeeding until six months of age, followed by the introduction of natural or minimally processed foods. Breast milk, in addition to providing emotional bonding, offers protection against overweight and obesity due to its bioactive compounds. However, the early introduction of foods, such as animal milk or processed foods, is common, which compromises adequate nutritional development and increases the risk of obesity and other chronic diseases. The introduction of ultra-processed foods before the first year of life is associated with these problems, and their prevalence is high in children under two years of age. (Souza et al 2021).